Manajemen e-Government Berbasis Web Model Government-to-Citizen (G2C) Pada Dinas Kebudayaan dan Pariwisata Provinsi Jambi - Dedek Kusnadi (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Information and Communication Technology / IC is very important in the era of globalization. At this time, electronic government (e-gov) has begun to develop as an implementation of the use of information and communication technology in regional and provincial governments. One of the E-gov applications in government organizations is the local or provincial government website. Like the Jambi Province Culture and Tourism Office which uses the government's website as the simplest tool for viewing e-Government, the content is still in the form of general information needed by the public as information seekers. The problem is how to manage the web-based Government-to-Citizen (G2C) e-Gov model at the Jambi Province Culture and Tourism Office. Gov at the Jambi Province Culture and Tourism Office. To answer this problem is to use the management function of G.R. terry. This study used an exploratory qualitative research design. The results of the study show that the G2C web-based e-Gov management model at the Jambi Province Culture and Tourism Office is in the second stage, namely maturation. This condition can be seen from the planning, organizing, implementing and controlling in culture and the Jambi Provincial Tourism Office. Obstacles in the management of e-Gov based on the G2C web model at the Jambi Province Culture and Tourism Office seen from the process of planning, organizing, implementing, controlling have not been optimal as a whole. Inadequate human resources, lack of outreach to the community, sectoral ego in several local government agencies, and lack of budget from local government. There have been several improvements and change management in several aspects of planning, organizing, implementing, and controlling. Increasing outreach to the community, having good budget planning, and increasing the ability of employees are suggestions for improvement.